A DATA PROCESSING PROGRAM FOR WEB BASED RAIN GAUGE CALIBRATORS - Maftukhah, Tatik; Wijonarko , Sensus (LIPI Press, Anggota IKAPI, 2019)
The purpose of this study was to produce an application program for the data processing unit of a web base rain gauge calibrator. The application program was developed using Studio XE2 of C ++ RAD (Rapid Application Development) software. Testing result shows that what you get was what you command or there was no different between the result and the command.